2021
DOI: 10.3390/biomedicines9091258
|View full text |Cite
|
Sign up to set email alerts
|

Master Regulators of Epithelial-Mesenchymal Transition and WNT Signaling Pathways in Juvenile Nasopharyngeal Angiofibromas

Abstract: Juvenile nasopharyngeal angiofibroma (JNA) is a rare fibrovascular benign tumor showing an invasive growth pattern and affecting mainly male adolescents. We investigated the role of epithelial–mesenchymal transition (EMT) and WNT signaling pathways in JNA. Gene expression profiles using nine JNA paired with four inferior nasal turbinate samples were interrogated using a customized 2.3K microarray platform containing genes mainly involved in EMT and WNT/PI3K pathways. The expression of selected genes (BCL2, CAV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…In the last decade, several studies described the involvement of specific genes and signaling pathways, such as Wnt, in JA progression [46]. In particular, Wnt5B, a member of the Wnt family, is overexpressed in JA [47]. Of note, CK2 acts as a positive regulator of Wnt signaling [48] and several studies have already suggested that pharmacological CK2 inhibition may be a promising therapeutic approach for the treatment of tumors with high Wnt activity, such as chronic lymphocytic leukemia and B-cell lymphomas [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, several studies described the involvement of specific genes and signaling pathways, such as Wnt, in JA progression [46]. In particular, Wnt5B, a member of the Wnt family, is overexpressed in JA [47]. Of note, CK2 acts as a positive regulator of Wnt signaling [48] and several studies have already suggested that pharmacological CK2 inhibition may be a promising therapeutic approach for the treatment of tumors with high Wnt activity, such as chronic lymphocytic leukemia and B-cell lymphomas [49,50].…”
Section: Discussionmentioning
confidence: 99%